De novo DNA methyltransferase DNMT3A: Regulation of oligomeric state and mechanism of action in response to pH changes - Holz-Schietinger, Celeste; Reich, Norbert O. (Biochimica et biophysica acta, 2015)
The oligomeric state of the human DNMT3A is functionally important and cancer cells are known to undergo changes in pH (intracellular). Light scattering, gel filtration, and fluorescence anisotropy. Also, methylation and processivity assays. Physiologically relevant changes in pH result in changes in DNMT3A oligomer composition which have dramatic consequences on DNMT3A function. The pH changes which occur within cancer cells alter the oligomeric state and function of DNMT3A which could contribute to changes in genomic DNA methylation observed in vivo. •We show that small changes in pH directly alter the function of the human DNMT3A.•Acidification from pH7.8 to 6.8 disrupts the dimer interface with a 10 fold loss of processive methylation.•Mutations occurring in AML patients alter this pH sensitivity.•The DNMT3A dimer interface is dynamic and environmentally directed pH changes may lead to changes in DNA methylation patterns.